Essays on Philippine publicly-listed holding firms an application of management theories - Lizares, Maria Regina Lucia M.
A three essay dissertation (TED) to understand Philippine publicly-listed holding firms collectively, through the lens of several management theories. It uses panel and and pooled cross-section regressions, and publicly available information of Philippine publicly-listed holding firms for the period 2009 to 2015, the era immediately after the last global financial crisis.